2-Mercaptobenzimidazole clubbed hydrazone for Alzheimer’s therapy: In vitro, kinetic, in silico, and in vivo potentials - Begum, Farida; Rehman, Najeeb Ur; Khan, Ajmal; Iqbal, Sajid; Paracha, Rehan Zafar; Uddin, Jalal; Al-Harrasi, Ahmed; Lodhi, Muhammad Arif (Frontiers in Pharmacology, 2022)
Alzheimer's is a type of dementia that disturbs the affected person's thinking, memory, and behaviour. It is a multifactorial disease, developed by the breakdown of the neurotransmitter acetylcholine via acetylcholinesterase (AChE). The present study was designed to evaluate potential inhibitors of acetylcholinesterase that could be used as a therapeutic agent against Alzheimer's disease (AD). For this course, synthetic compounds of Schiff bases class of 2-Mercaptobenzimidazole hydrazone derivatives (9-14) were determined to be potent acetylcholinesterase inhibitors with IC50 values varying between 37.64 ± 0.2 to 74.76 ± 0.3 μM. The kinetic studies showed that these are non-competitive inhibitors of AChE. Molecular docking studies revealed that all compounds accommodate well in the active site and are stabilized by hydrophobic interactions and hydrogen bonding. Molecular dynamics (MD) simulations of selected potent inhibitors confirm their stability in the active site of the enzyme. Moreover, all compounds showed antispasmodic and Ca2+ antagonistic activities. Among the selected compounds of 2-Mercaptobenzimidazole hydrazone derivatives, compound 11 exhibited the highest activities on spontaneous and K+-induced contractions, followed by compound 13. Therefore, Ca2+ antagonistic, AChE inhibition potential, and safety profile of these compounds in human neutrophils viability assay make them potential drug candidates against AD in future.